Tindak Tutur Ilokusi Prof. J. E. Sahetapy dalam Talk Show ILC (Indonesia Lawyers Club) di TV One - Elsye Jesti Mutji (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2017)
Speech acts not only to say something but also everyone has purpose in every word they said in communication. Illocutionary acts is a speech acts used not only to say something but also to do something. The aims of this research are (1) to identify and analyze the function of illocutionary acts by Prof. J. E. Sahetapy in ILC (Indonesia Lawyers Club) talk show in TV One and (2) to determine illocutionary acts politeness by Prof. J. E. Sahetapy on that talk show. Method used in this research is qualitative descriptive method and the collecting data techniques used are observation and noting. Data resources are taken randomly from ILC (Indonesia Lawyers Club) talk show video on you tube with eight different titles from September 2009 – Mei 2014. Theoretical frame used is Leech Concept (1993) to analyze illocutionary act function by Prof. J. E. Sahetapy and to determine the politeness of illocutionary acts by Prof. J. E. Sahetapy is Lakoff Theory in Chaer (2010). It can can be concluded that the function of illocutionary acts by Prof. J. E. Sahetapy on ILC (Indonesia Lawyers Club) talk show, supporting Leech Concept (1993) about function of illocutionary acts. There are four functions found: competitive, convivial, collaborative and conflictive. These findings support Lakoff Theory on Chaer (2010) as found three scales of politeness: formality scale, hesitancy scale and equality scale. The research “Illocutionary Acts by Prof. J. E. Sahetapy in ILC (Indonesia Lawyers Club) Talk Show only identify illocutionary acts, functions and politeness, so further research needs to be conducted.